Reflecting on educational research in ICT - Cabero-Almenara, Julio; Valencia-Ortiz, Rubicelia (Innovaciones Educativas, 2021)
Despite the evolutionary process that educational research focused on Information and Communication Technologies (ICT) has undergone, it still does not offer answers to teachers to incorporate them and thereby transform educational practice. This complex situation requires asking a question: what have we learned from past research to find more successful proposals for use based on the results achieved? Based on the answers to this dilemma, this article reflects on the need to channel ICT research in new directions, with new methodologies, new research designs and orientations towards new problems.